The Impact of Industrialisation on Zambia's Economic Growth - Yangailo, Tryson; Chambani, Taonga (Universitas Airlangga, 2023)
This research study examines the impact of industrialisation on economic growth in Zambia. The study utilised secondary data from Zambian Central Bank and Word-Bank data statistics. The research did specify the model, where GDP was dependent (outcome) variable whereas, FDI, industrial output, interest rate, inflation and currency exchange rate were the independent (predictor) variables. Regression-analysis was used to analyse data using Jamovi-software. The study presents that industrialisation has a positive significant impact on Zambia's economic growth.